If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(X-1)(X+1)X(X+2)=24
We move all terms to the left:
(X-1)(X+1)X(X+2)-(24)=0
We use the square of the difference formula
X^2-1-24=0
We add all the numbers together, and all the variables
X^2-25=0
a = 1; b = 0; c = -25;
Δ = b2-4ac
Δ = 02-4·1·(-25)
Δ = 100
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{100}=10$$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-10}{2*1}=\frac{-10}{2} =-5 $$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+10}{2*1}=\frac{10}{2} =5 $
| (5x+3)^1/2=3 | | --18=15z-9(2z-2) | | 2(3w+6)/3=9 | | 22-2x=3x | | 4(f-9)=0 | | 2^(2x-3)=8 | | -8(s+5)=-84 | | 14-3x=2x | | 7(2x-4)=3x-8 | | 7(2x-4=3x-8 | | x/12=96 | | 2x²+5x-5+x²+11x-7=180 | | 4(2l+9)=116 | | 4x=15-3x | | (q-7)*4=32 | | (q-7)*47=32 | | (3x-2)^2=4 | | 2(x+8)+3(x–4)=19 | | √(5x-1)=-1 | | 40^2+15^2=c^2 | | 12x16=285 | | 12/6=8/x | | 10=4c-74 | | b^2-19b=240 | | 10=4c=74 | | x^2+40x-1425=0 | | 1+1/4(x-2)=21/2 | | 14.6+x=284.7 | | 8y+3+(12-7y)=49 | | (4x-3)/(2x-5)=0 | | 5x+19x-6=6(4x+5) | | (2x+5)-(4x+6)=10 |